2016
DOI: 10.1111/petr.12805
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine prior to salvaged unrelated cord blood transplantation for refractory or relapsed childhood acute leukemia

Abstract: No clinical studies have investigated the role of decitabine as a part of the myeloablative conditioning regimen prior to UCBT for refractory or relapsed childhood AL in patients in NR status. The aim of this study was to identify the potential benefits of decitabine as a prior therapy before salvaged unrelated UCBT for refractory or relapsed childhood AL. Eight consecutive patients with childhood refractory/relapsed AL were enrolled in our study between 2013 and 2014. All patients were in NR status before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This systematic review has included 20 studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] after screening over one thousand records and applying eligibility criteria to studies identified during the literature search (Figure 1). In these studies, 310 refractory or relapsed AML patients were treated with decitabine in combination with one or more drugs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review has included 20 studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] after screening over one thousand records and applying eligibility criteria to studies identified during the literature search (Figure 1). In these studies, 310 refractory or relapsed AML patients were treated with decitabine in combination with one or more drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Liesveld et al [26] 2013 DAC (20 mg/m 2 IV daily for 5 days) with rapamycin on day 6 to day 25 at doses of 2, 4, and 6 mg/day in a standard 3 + 3 dose escalation design Mims et al [27] [36] 2016 DAC (20 mg/m 2 /day) for 3-5 days with aclacinomycin (10 mg/m 2 × 5 days), Ara-C (10 mg/m 2 q12 × 10-14 days), and granulocyte colony stimulating factor (150 μg/day for 10-14 days) Zhao et al [37] 2017 DAC (20 mg/m 2 /day on days 1-5) and Idarubicin 10 mg/m 2 /day on days 6-8, and cytoarabine 100 mg/m 2 twice daily on days 6-10 Zhou et al [38] (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…34 Mechanisms of tumor immune evasion focus on the downregulation of class I and II HLA expression, together with the downregulation of NK cell targets. 35,36 The addition of HMAs could overcome such immune evasion because of their ability to upregulate the expression of epigenetically silenced tumor-associated antigens 37 and PD-L1, 38 which subsequently activate antigen-specific T cell responses. Furthermore, decitabine can expand NK cell and CD8+ T cell populations and enhance NK cell-mediated antibody-dependent cellular cytotoxicity against leukemia cells, demonstrating an increased graft-vsleukemia (GVL) capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Decitabine (Dec), a hypomethylating agent (HMA) that irreversibly inhibits DNA methyltransferase I and induces leukemic differentiation and reexpression of epigenetically silenced putative tumor antigens, has been shown to be efficacious for a broad range of hematologic disorders, including MDS, acute myelogenous leukemia (AML), chronic myelomonocytic leukemia (CMML), and sickle cell anemia [9][10][11][12]. The use of Dec before and after allo-HSCT is reported to help eradicate minimal residual disease, decrease the incidence of GVHD, and facilitate the GVL effect by enhancing the effect of T regulatory lymphocytes [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The use of Dec before and after allo-HSCT is reported to help eradicate minimal residual disease, decrease the incidence of GVHD, and facilitate the GVL effect by enhancing the effect of T regulatory lymphocytes [13,14]. The addition of HMAs to such a conditioning regimen could have a dual effect because of their Biology of Blood and Marrow Transplantation journal homepage: www.bbmt.org ability to up-regulate the expression of epigenetically silenced tumor-associated antigens, which subsequently evoke specific T cell responses [8,12].…”
Section: Introductionmentioning
confidence: 99%